2005
DOI: 10.1111/j.1447-073x.2005.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the respiratory tract of the red-bellied newt Cynops pyrrhogaster, with reference to serotonin-positive neuroepithelial endocrine cells

Abstract: To investigate the distribution of serotonin-positive neuroepithelial endocrine (NEE) cells in the respiratory tract of the red-bellied newt Cynops pyrrhogaster, serial sections of the respiratory tract were stained using immunohistochemical methods for serotonin, a periodic acid-Schiff method and hematoxylin-eosin staining. The respiratory tract of the red-bellied newt consisted of a tubular laryngotrachea and two pulmonary sacs. Serotonin-positive solitary NEE cells were distributed widely throughout the cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, the tracheal cells of Pseudemys scripta elegans were positive only to PAS and AB pH 2.5 (Pastor et al, 1987a). According to Naruse et al (2005), the cilia and mucous secreted by goblet cells in the epithelium represent the first line of airway defence after exposure to infection, pollution, toxins or inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tracheal cells of Pseudemys scripta elegans were positive only to PAS and AB pH 2.5 (Pastor et al, 1987a). According to Naruse et al (2005), the cilia and mucous secreted by goblet cells in the epithelium represent the first line of airway defence after exposure to infection, pollution, toxins or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin immunoreactive cells in the respiratory system may possibly play an important role in the defense and repair of the ciliomucous epithelium, such as increasing mucus secretion, ciliary beat frequency and proliferation of epithelial cells (Naruse et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The present results show that there is a close relation between these cells and the FSCs of the pharyngeal groves and gill seam. Studies carried out in echinoderms (Wada et al,1997), gastropods (Diefenbach et al,1991; McKenzie et al,1998; Uhler et al,2000; Doran et al,2004; Braubach et al,2006), mollusks (Pavlova et al,1999; Kuang and Goldberg,2001; Koss et al,2003), and amphibians (Maruyama et al,1984a,b; Naruse et al,2005) showed that 5‐HT plays a key role in the control of mucus secretion and ciliary beat frequency. The close relation between 5‐HT‐ir FSCs and the ciliated and mucous epithelia observed in lamprey may indicate that these cells are also involved in the control of the ciliary beat and mucus secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, DNES (Diffuse Neuro Endocrine System) has taken place of APUD (14,19,20,35). The systems which are constitued by these cells are called gastroenteropancreatic (GEP) system or gastroenteropancreatic-neuroendocrine system (1,13,20,22,35).…”
Section: Introductionmentioning
confidence: 99%